(untitled) (Revista de Ciências Agroveterinárias, 2025)
This work sought to evaluate the effects of the use of basalt powder on the development of bean (Phaseolus vulgaris) crops in a biodynamic production system. The experiment, conducted in the field, in the biodynamic space of the Center for Rural Sciences (CCR) of the Federal University of Santa Catarina (UFSC), located in the city of Curitibanos-SC, was done through a Randomized Block Design (DBC) with three treatments: T1 control (without the use of basalt powder), T2 dosage of 2 t/ha of basalt powder and T3 dosage of 3t/ha of basalt powder. All treatments received the biodynamic preparations PB 500, Fladen and PB 501, in addition to the poultry litter at a dosage of 3 t/ha. The research methodology consisted of performing Analysis of Variance (ANOVA) and Tukey’s Test to compare the plant height averages of each treatment after 30 days of planting and dry weight of harvested beans. In addition, Polynomial Regression Analysis was performed, along with the calculations of Maximum Technical Efficiency (TEM) and Maximum Economic Efficiency (MEE) to stipulate the optimal point of economic viability of the application of basalt powder. The results indicated that T2 and T3 showed higher initial vegetative growth (plant height) in comparison to T1; T3 differed from T1 in yield (weight of dry grains) and that the economic viability of using basalt powder in the biodynamic system, considering only the current prices of the input-output ratio, has its optimal point of TEM at 0.61 t/ha and MEE at 0.59 t/ha. With this, it is concluded that there are indications of positive effects of the application of basalt powder for bean yield in the biodynamic system and that the technical and economic feasibility studies need to be improved due to the slow pace of nutrient availability of basalt powder.